Red emissive two-photon carbon dots: Photodynamic therapy in combination with real-time dynamic monitoring for the nucleolus. (September 2021) - Yi, Shangzhao; Deng, Simin; Guo, Xiaolu; Pang, Congcong; Zeng, Jinyan; Ji, Shichen; Liang, Hong; Shen, Xing-Can; Jiang, Bang-Ping
Abstract: Treatment in combination with real-time monitoring of dynamic organelle changes is of great significance for evaluating therapeutic efficacy. However, it remains highly challenging to realize such specific treatment and monitoring in organelles. Herein, we developed one kind of red emissive two-photon carbon dots (TP-CDs) via an N doping strategy for nucleolus-targeted treatment combined with real-time monitoring of dynamic changes in the nucleolus. In the TP-CD system, N doping endows TP-CDs with intrinsic two-photon excitation, red emission at 605 nm, and singlet oxygen ( 1 O2 ) production under 638 nm laser irradiation. More importantly, N heterocycles induced by doping offers significant affinity for TP-CDs toward RNA to realize specific self-targeting toward nucleolus and fluorescence variation during the photodynamic therapy (PDT) via the cleaving of RNA chain by 1 O2 to dissociate TP-CDs@RNA complex. By combining 1 O2 production, fluorescent variation during the PDT process, long-wavelength excitation and emission characteristics, as well as specific self-targetability of nucleolus, TP-CDs can be considered as a kind of "smart" CDs to realize treatment in combination of real-time dynamic changes in nucleolus for the first time. Graphical abstract: Image 1